2006
DOI: 10.1007/s10549-006-9437-z
|View full text |Cite
|
Sign up to set email alerts
|

Mid-region parathyroid hormone-related protein (PTHrP) binds chromatin of MDA-MB231 breast cancer cells and isolated oligonucleotides “in vitro”

Abstract: We have previously shown that PTHrP(38-94)-amide restrains growth and invasion "in vitro", causes striking toxicity and accelerates death of some breast cancer cell lines, the most responsive being MDA-MB231 whose tumorigenesis was also attenuated "in vivo". PTHrP(38-94)-amide contains the domain implicated in the nuclear import of PTHrP. Although the nucleus was identified as a destination for mid-region PTHrP, evidence for direct DNA-binding capability is lacking to date. Here, we examined the localization o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
(47 reference statements)
1
20
0
Order By: Relevance
“…More recently, evidence was produced that midregion PTHrP is imported in the nucleoplasm of cultured MDA-MB231 cells, and that ''in vitro'' it can bind chromatin of metaphase spread preparations and also an isolated 20-mer oligonucleotide, thereby appearing endowed with a putative transcription factor-like DNA-binding ability [23]. This is consistent with data indicating that midregion PTHrP possesses a nuclear targeting signal (NTS) encompassing aminoacids 87-107 and that the lysine-rich 84-93 domain is per se able to direct importin b/Ran GTPase-mediated import of to the nucleoplasm under the control of phosphorylation/dephosphorylation events in T 85 [24, for review].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, evidence was produced that midregion PTHrP is imported in the nucleoplasm of cultured MDA-MB231 cells, and that ''in vitro'' it can bind chromatin of metaphase spread preparations and also an isolated 20-mer oligonucleotide, thereby appearing endowed with a putative transcription factor-like DNA-binding ability [23]. This is consistent with data indicating that midregion PTHrP possesses a nuclear targeting signal (NTS) encompassing aminoacids 87-107 and that the lysine-rich 84-93 domain is per se able to direct importin b/Ran GTPase-mediated import of to the nucleoplasm under the control of phosphorylation/dephosphorylation events in T 85 [24, for review].…”
Section: Introductionmentioning
confidence: 99%
“…This approach is in line with the work by other authors to obtain a detectable effect of PTHrP and its fragments in in vitro studies. (19,41,57) In conclusion, we have identified novel pathogenetic functions of PTHrP in MM related to tumor survival, proliferation, and OC hyperactivation. Because serum elevation of PTHrP in patients with solid tumors produces severe skeleton devastation and leads to a poor prognosis, a systematic analysis of PTHrP levels in MM patients would be advisable, to determine whether this peptide is a novel marker of disease progression.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, the NLS þ mid-region (aa 38-94) is proteolytically degraded in cytoplasm and internalized by nuclei where this fragment primes in an intracrine fashion the proliferation of MM cells by its complementarity to the 5 0 -GAGTAGAATTCTAA-TATCTC-3 0 DNA sequence. (19) Other authors, however, have suggested that, to induce a similar effect, the NLS subunit may be transported and internalized in nuclei by cytoplasmic importin-b and that this mechanism is protective for tumor cells in preventing their apoptosis or anoikis induced by starvation. (41,42,46) By contrast, an opposite proapoptogenic effect has been ascribed to the NLS þ mid-region (aa 38-94) in cell kinetic analysis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations